60=3(x=3)

Simple and best practice solution for 60=3(x=3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60=3(x=3) equation:



60=3(x=3)
We move all terms to the left:
60-(3(x)=0

See similar equations:

| 9x^2-55x+56=0 | | -(x+3-x)=x-7 | | Y=2x2+76 | | s/4+5=9 | | x/9(x-2)=27 | | n-7/2=n/9 | | 7x+17=9x-25 | | 21​ (6x+8)=3121​ 1/2(6x+8)=31 | | q−78–2=–6 | | (s+75=105) | | -(-5+9r)+7=-51 | | s4+5=9 | | -62-2x=57-9x | | x3+1x=27 | | s/4+ 5=9 | | f/2+8=12 | | 8x-6-x=-6-2x+6x | | 3(x=2)+x-5=7(x+1)-6 | | 8x-3=10-5 | | 7y-11+4y=-55 | | -3y(5y-3)-y=-2(y-5) | | 23=-3w-13 | | −6(2+6a)=−120 | | -2x-139=9x+48 | | -(-5+9r)7=-51 | | 3x−2(4x+5)=4x+x+20 | | −5(1−5w)+5(−8w−2)=−7w−2w−7w-5(1-5w)+5(-8w-2)=-7w-2w-7w | | -3x+7=-5x+8 | | 4m+8m=16+8m | | x3+1=27 | | 2x+2=–52 | | 5f=1/5 |

Equations solver categories